2020
DOI: 10.21608/ajnsa.2020.16698.1266
|View full text |Cite
|
Sign up to set email alerts
|

Production of Polyhydroxybutyrate (PHB) from Streptomyces Incanus and the Effect of Gamma Irradiation on its Production

Abstract: Polyhydroxybutyrate (PHB) is a biosynthetic and biodegradable plastic which attracts attention du to its properties. Out of nine Actinomycetes isolates obtained from different soil samples, the PHB accumulating isolate was identified by molecular studies and was identified as Streptomyces incanus BK128. Different agricultural waste (wheat bran, rice bran, rice straw and molasses) were employed for polyhydroxybutyrate (PHB) production as the main carbon source. Some supplements such as (0.4 g) ammonium sulphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Species of the genus Bacillus have the ability to utilize these diverse and cheap carbon wastes, as they possess hydrolytic enzymes capable of metabolizing these complex residues. Different agricultural waste materials (wheat bran, rice bran, rice straw, and molasses) were employed as the main carbon source for PHB production by Streptomyces incanus [14], and wheat bran has the highest PHB production of 2.82 g/L. In this study, the carbon source was replaced by the extracts of five different agricultural waste materials including orange peel, banana peel, mango peel, onion peel, and rice straw for PHB production.…”
Section: Production Of Phb From Waste Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Species of the genus Bacillus have the ability to utilize these diverse and cheap carbon wastes, as they possess hydrolytic enzymes capable of metabolizing these complex residues. Different agricultural waste materials (wheat bran, rice bran, rice straw, and molasses) were employed as the main carbon source for PHB production by Streptomyces incanus [14], and wheat bran has the highest PHB production of 2.82 g/L. In this study, the carbon source was replaced by the extracts of five different agricultural waste materials including orange peel, banana peel, mango peel, onion peel, and rice straw for PHB production.…”
Section: Production Of Phb From Waste Materialsmentioning
confidence: 99%
“…Mostafa and his coworkers [13] isolated novel strains of PHB-producing bacteria (Tamlana crocina, Bacillus aquimaris, Erythrobacter aquimaris, and Halomonas halophila) from the mangrove rhizosphere, Red Sea, Saudi Arabia, which can make PHB production a decent contender for numerous industrial applications as a substitution for petroleum-based plastics. Rezk et al (2020) [14] proved that wheat bran can be used as an alternative to starch nitrate medium for PHB production by Streptomyces incanus BK128.…”
Section: Introductionmentioning
confidence: 99%
“…Rare actinomycetes Aquabacterium sp., A7-Y produced 10.2 g/L of PHB in 5 L fed-batch fermenter after optimization [45]. Streptomyces incanus BK 128 which was isolated from the Rhizosphere of eggplant by Rezk et al [46] used for production of PHB biopolymer using different agricultural waste synthesized maximum quantity of 2.82 g L -1 .…”
Section: Interpretation Of Phb Production By Different Microorganismsmentioning
confidence: 99%
“…The production of PHB is expected to be a good replacement for petroleum-based plastics in a number of industrial applications. A study reported by Rezk et al [ 31 ] showed that wheat bran could be used as a substitute for starch nitrate medium for the production of PHB by Streptomyces incanus BK128. Danial et al [ 32 ] isolated the B. wiedmannii AS-02 OK576278 strain, which was capable of producing PHB when pre-treated with various agricultural residues such as onion peels, banana peels, mango peels, orange peels, mango and rice straw were used as the carbon sources, respectively.…”
Section: Introductionmentioning
confidence: 99%